Model of judicial management of evidence-taking proceedings in the Italian civil trial (Cartabia Reform) (Ius Novum, 2024)
The article presents a model of judicial management of the evidence-taking proceeding in the Italian civil procedure after the reform introduced based on Law No. 206 of 26 November 2021, implemented, inter alia, on 28 February 2023 and on 30 June 2023 by means of Legislative Decree No. 149 of 10 October 2022 (the reform was named after its author, former Minister of Justice Marta Cartabia: riforma Cartabia). After the reform, the model was significantly formalised and made more detailed, not leaving much decision-making freedom in the field of organising a proceeding to the judge. From the perspective of the principle of the procedural material concentration and the judicial management of the evidence-taking proceeding, the most important stage of the proceeding is its preliminary stage: from the moment the plaintiff summons the defendant to court (in ius vocatio), which is in fact a lawsuit, to the hearing intended for the first appearance of the parties and the case verification. At this stage of the proceeding, the parties are obliged to clearly and substantially present facts, legal elements of a claim, means of evidence and all defence arguments in their pleadings submitted within statutory deadlines. The next stage of collecting procedural material important for the resolution of the case is a hearing scheduled for the first appearance of the parties and verification of the case (it can be called a preliminary hearing). At this hearing, the judge freely questions the parties and, based on the facts presented, explains the matters necessary to resolve the case. Having questioned the parties, the court may take a decision to conduct a conciliation proceeding. If such a decision is not made, the judge decides on the parties’ evidence related motions and, taking into consideration the nature, urgency and complexity of the case, renders a decision on the timetable of subsequent hearings and indicates actions that will be taken at each of them. A hearing intended for the taking of evidence admitted should be scheduled within 90 days. The court may also rule the taking of evidence ex officio. Then, the judge conducting this proceeding, in accordance with the timetable he has developed, takes evidence. The final stage of an ordinary proceeding takes place when the judge recognises that the case is mature enough to be resolved because it has been appropriately and definitively prepared and the necessary evidence has been collected, or there is no need to collect it. One of the tools used to manage an evidence-taking proceeding may be the so-called abuse of procedural law. The Italian civil procedure does not explicitly regulate it. The concept of abuse of procedural law has been defined in case law and the doctrine. However, the procedural regulations provide for the obligation to act in court in accordance with the principle of honesty and loyalty. Various sanctions are also stipulated for conduct that violates this obligation, such as e.g. the obligation to pay compensation, order to reimburse for trial costs, or imposition of a fine.
Keywords: Cartabia reform, judicial management of a proceeding, evidence-taking proceeding, in ius vocatio, preliminary hearing, Italian civil procedure, principle of honesty and loyalty